Analysis of the Hadith ‘A people who make a woman their ruler will never be successful.’ as Tafsir bi al-Ma'tsur from Surah al-Nisa: 34 - Mustopa (Journal of Islamicate Studies, 2024)
The hadith that reads "A people who make a woman their ruler will never be successful" has become the subject of discussion on the role of women's leadership in Islam. This article analyzes the hadith with the tafsir bi al-ma'tsur approach, especially in relation to Surah al-Nisa: 34, which discusses the role and responsibility of gender in the family and society. Through a study of classical and contemporary literature, this article explores the scholars' understanding of this hadith as well as how it is used in the interpretation of Qur'anic verses that govern the hierarchy of leadership in households and society. This article also considers the social and legal implications of such an understanding in a modern context, by reviewing its relevance to discussions about gender equality and the role of women in leadership.